Industrial labor on the margins of capitalism : precarity, class, and the neoliberal subject - Hann, C. M.; Parry, Jonathan P. (Max Planck studies in anthropology and economy, 2018)
Bringing together ethnographic case studies of industrial labor from different parts of the world, Industrial Labor on the Margins of Capitalism explores the increasing casualization of workforces and the weakening power of organized labor. This division owes much to state policies and is reflected in local understandings of class. By exploring this relationship, these essays question the claim that neoliberal ideology has become the new `commonsense' of our times and suggest various propositions about the conditions that create employment regimes based on flexible labor.
Keywords: Working class; Labor movement; työväenluokka; työväenliike; prekariaatti